2017
DOI: 10.1007/s40520-017-0821-9
|View full text |Cite
|
Sign up to set email alerts
|

The value of C-reactive protein in infection diagnosis and prognosis in elderly patients

Abstract: In elderly patients with infection, the initial CRP value alone does not have prognostic value, but changes observed in serial CRP measurement are a valid indicator of prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In our cohort of elderly patients, we did not find that CRP level at admission was associated with one-year mortality. In a similar population, Karasahin et al described that monitoring changes in serial CRP measurements could be useful for prognosis in elderly patients with infection [ 37 ]. They showed that a CRP decrease less than 11% over 48 h and less than 20% over 96 h was a risk factor for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort of elderly patients, we did not find that CRP level at admission was associated with one-year mortality. In a similar population, Karasahin et al described that monitoring changes in serial CRP measurements could be useful for prognosis in elderly patients with infection [ 37 ]. They showed that a CRP decrease less than 11% over 48 h and less than 20% over 96 h was a risk factor for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…They rapidly recruit and phagocytose to kill pathogenic microorganisms after bacterial infections ( Kobayashi et al., 2018 ), so they will show an increase after infection. CRP is one of the most distinctive indicators of inflammation, involvement in the inflammatory response in vivo through complement activation and receptor-mediated modalities, exhibiting different levels at different time points of pathogenic infection ( Karasahin et al., 2018 ; Luo et al., 2020 ). The normal range of CRP is 0-10mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…In a previously published article, lower CRP clearance, which determined the difference of serial measurements, was a mortality indicator. 28 CRP is also a useful indicator for various conditions. Higher mortality, and more operations and ICU admissions were in high-CRP group in abdominal surgery (cut-off: 15 mg/dL).…”
Section: Discussionmentioning
confidence: 99%